Preparticipation cardiovascular screening of young athletes. An epidemiologic perspective - Wen, D. Y. (The Physician and Sportsmedicine, 2005)
Sudden cardiac death in young competitive athletes is a rare—but often highly publicized—event. Preparticipation screening for potentially lethal cardiovascular conditions is a complicated and controversial issue. Clinicians need a firm grasp of sound epidemiologic principles concerning screening programs when using the history and physical examination, echocardiography, and electrocardiography to detect potential problems. The very low prevalence of potentially lethal conditions and the low sensitivity and low specificity of the available methods of detection, used alone or in combination, render the positive predictive value of these screening methods exceedingly low.